Cachexia index as a biomarker for cancer cachexia and quality of life in patients with gastric cancer - Yan Huang; Zhenhua Huang; Wenji Hou; Chen Wang; Xiuhua Wang; Junbo Zuo (BMC Cancer)
Abstract Background Cachexia is associated with adverse clinical outcomes in patients with gastric cancer (GC); therefore, a convenient and reliable method for monitoring cachexia is essential. This study aimed to evaluate the utility of the cachexia index (CXI) as a biomarker for estimating cancer cachexia and health-related quality of life (HRQoL) in GC patients. Methods The CXI was calculated as the skeletal muscle index (SMI) × serum albumin / neutrophil–lymphocyte ratio (NLR). Diagnosis of cachexia was based on Asian Working Group for Cachexia (AWGC) criteria and Fearon’s criteria. Univariate and multivariate logistic regression analyses were carried out to identify potential risk factors related to cancer cachexia and HRQoL respectively. Receiver Operating Characteristics (ROC) analysis was conducted to evaluate the diagnostic value in identifying cancer cachexia, and the area under the ROC curve (AUC) was calculated. Results This study comprised a total of 431 patients diagnosed with GC, including 309 males (71.7%) and 122 females (28.3%), with a median age of 68 years. Compared to patients without cachexia, the CXI values were significantly lower in those with cachexia defined by either the AWGC criteria or Fearon’s criteria (p < 0.001). After adjusting for potential confounding factors in the multivariate logistic analysis, CXI was found to be independently associated with AWGC-defined cachexia (OR = 0.98, 95% CI: 0.97–0.99, p < 0.001), but not with Fearon-defined cachexia (OR = 1.00, 95% CI: 0.99–1.01, p = 0.601). Based on ROC curve analysis, the AUC was 0.752 for males and 0.717 for females, with cut-off CXI values of 74.46 and 43.80 for identifying AWGC-defined cachexia, respectively. Patients with low CXI demonstrated greater severity in major aspects of HRQoL, and low CXI was independently associated with poor HRQoL (OR = 1.79, 95% CI = 1.05–3.07, p = 0.033). Conclusions CXI could serve as a useful biomarker for evaluating cancer cachexia and HRQoL in patients with GC.